Answer:
the answer for this question is (y-5)/4=x
Answer:
or ![x = -5](https://tex.z-dn.net/?f=%20x%20%3D%20-5%20)
Step-by-step explanation:
You need to complete the square before you can take the square root of both sides.
![x^2 + 7x + 10 = 0](https://tex.z-dn.net/?f=%20x%5E2%20%2B%207x%20%2B%2010%20%3D%200%20)
Subtract 10 from both sides.
![x^2 + 7x = -10](https://tex.z-dn.net/?f=%20x%5E2%20%2B%207x%20%3D%20-10%20)
To complete the square, you need to add the square of half of the x-term coefficient to both sides.
The x-term coefficient is 7. Half of that is 7/2. Square it to get 49/4. Now we add 49/4 to both sides of the equation.
![x^2 + 7x + \dfrac{49}{4} = -10 + \dfrac{49}{4}](https://tex.z-dn.net/?f=%20x%5E2%20%2B%207x%20%2B%20%5Cdfrac%7B49%7D%7B4%7D%20%3D%20-10%20%2B%20%5Cdfrac%7B49%7D%7B4%7D%20)
![(x + \dfrac{7}{2})^2 = -\dfrac{40}{4} + \dfrac{49}{4}](https://tex.z-dn.net/?f=%20%28x%20%2B%20%5Cdfrac%7B7%7D%7B2%7D%29%5E2%20%3D%20-%5Cdfrac%7B40%7D%7B4%7D%20%2B%20%5Cdfrac%7B49%7D%7B4%7D%20)
![(x + \dfrac{7}{2})^2 = \dfrac{9}{4}](https://tex.z-dn.net/?f=%20%28x%20%2B%20%5Cdfrac%7B7%7D%7B2%7D%29%5E2%20%3D%20%5Cdfrac%7B9%7D%7B4%7D%20)
Now we use the square root property, if
, then
![x = \pm \sqrt{k}](https://tex.z-dn.net/?f=%20x%20%3D%20%5Cpm%20%5Csqrt%7Bk%7D%20)
![x + \dfrac{7}{2} = \pm \sqrt{\dfrac{9}{4}}](https://tex.z-dn.net/?f=%20x%20%2B%20%5Cdfrac%7B7%7D%7B2%7D%20%3D%20%5Cpm%20%5Csqrt%7B%5Cdfrac%7B9%7D%7B4%7D%7D%20)
![x + \dfrac{7}{2} = \pm \dfrac{3}{2}](https://tex.z-dn.net/?f=%20x%20%2B%20%5Cdfrac%7B7%7D%7B2%7D%20%3D%20%5Cpm%20%5Cdfrac%7B3%7D%7B2%7D%20)
or
or ![x = -\dfrac{10}{2}](https://tex.z-dn.net/?f=%20x%20%3D%20-%5Cdfrac%7B10%7D%7B2%7D%20)
or ![x = -5](https://tex.z-dn.net/?f=%20x%20%3D%20-5%20)
Answer:
How do I keep falling for this trick!???
Answer:
expression equivalent given question is <em><u>93 - 8 x.</u></em>
<em><u>mark this as brainliest!</u></em>